2023
DOI: 10.3390/agronomy13092395
|View full text |Cite
|
Sign up to set email alerts
|

Fenlong-Ridging Deep Tillage Integrated with Biochar and Fertilization to Improve Sugarcane Growth and Yield

Jiming Xiao,
Shuifang Zhu,
Shijian Han
et al.

Abstract: Sugarcane yield in China is low because of the shallow A-horizon soil layer, or as it is commonly called by farmers, the “plow soil layer”, as well as low soil organic matter and fertilizer utilization efficiency. Fenlong-ridging deep tillage (FT), also called vertical rotary tillage, and amendment with biochar have been shown to improve soil quality and crop yield. In this study, field trials were conducted with newly planted and ratoon sugarcane to evaluate the effectiveness of FT, together with amendment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…However, in a potato experiment on a semiarid Loess Plateau, the researchers suggested that the crop water consumption of VRT was not reduced compared to deep rotary tillage and traditional tillage [46]. This discrepancy may be due to the deeper tillage depth (0-300 cm vs. 0-200 cm in the potato experiment) of the deep vertical rotary tillage used in this study, facilitating root penetration and increasing the root uptake of soil moisture in the research areas [40]. Further research is necessary to explore the ecological effects on the mineralization losses of soil organic matter and the applicability of deep vertical rotary tillage in farmland across different climatic regions [35].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, in a potato experiment on a semiarid Loess Plateau, the researchers suggested that the crop water consumption of VRT was not reduced compared to deep rotary tillage and traditional tillage [46]. This discrepancy may be due to the deeper tillage depth (0-300 cm vs. 0-200 cm in the potato experiment) of the deep vertical rotary tillage used in this study, facilitating root penetration and increasing the root uptake of soil moisture in the research areas [40]. Further research is necessary to explore the ecological effects on the mineralization losses of soil organic matter and the applicability of deep vertical rotary tillage in farmland across different climatic regions [35].…”
Section: Discussionmentioning
confidence: 68%
“…Research has demonstrated that deep vertical rotary tillage technology substantially enhanced effective soil water storage for sugarcane (Saccharum spp.) in southern China [40]. During dry years, this technology increased soil water storage (SWS) by 81.8% to 136.9% in the 0-200 cm soil layer, and by 34.3% to 86.9% during normal years, indicating its significant drought resistance [41].…”
Section: Discussionmentioning
confidence: 99%